ANALYSIS OF THERMAL INJURIES DEATHS IN A TERTIARY CARE HOSPITAL OF DELHI- A FIVE YEAR STUDY (Journal of Forensic Medicine & Toxicology, 2024)
The present retrospective study was conducted on 5477 cases of death due to thermal injuries during the period from January 2007 to December 2012 at Department of Forensic Medicine, Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi. The data were analysed with regard to age, sex, geographical distribution, type of inquest, mode of infliction, survival period, cause and manner of death. Most of the victims were females (61.26%) with male to female ratio 1:1.6. The peak incidence was seen in the age group of 21-30 years (42.92%). Inquest was done by police in 83.57% of cases followed by magistrate (16.43%). Majority of the victims were from Uttar Pradesh (42.36%) followed by Delhi (22.55%) and Haryana (19.79%). The most common manner of burn was accidental (85.24%), followed by suicidal (11.37%) and homicidal (3.39%). The mean survival period of all the victims was 6.4 days and majority (65.52%) of them died due to septicemia. Associated injuries contributing to death were present in 17 cases (0.32%).
Keywords: Burn; Accidental; Suicidal; Homicidal; Magistrate; Inquest; Septicemia